2013
DOI: 10.4236/health.2013.52030
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aquatic exercise on depression and anxiety in ischemic stroke subjects

Abstract: Background: Stroke ranks third and is the leading cause of permanent disability in western countries. Furthermore there are no treatments for the psychosocial effects of this pathology. Purpose: Analyse the effect of an aquatic exercise program in depression and trace and state anxiety in subjects who suffered an ischemic stroke. Methods: Two groups were analyzed: experimental group (EG) n = 15, 50.3 ± 9.1 years; control group (CG) n = 13, 52.5 ± 7.7 years. EG underwent a 12-week aquatic exercise program. Both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 44 publications
(44 reference statements)
0
9
0
5
Order By: Relevance
“…There is evidence that exercise improves psychological symptoms associated with poor health-related quality of life. 19 Nevertheless, some patients avoid exercise following a cardiac-related diagnosis or event 7 due to uncertainty about safety and appropriateness and lack of support. 4,35 This was echoed in our study; a number of respondents noted that although they were eager to do physical activity, with limited personalised guidance they were afraid they may push themselves too far, restricting the amount of exercise they were mentally comfortable doing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is evidence that exercise improves psychological symptoms associated with poor health-related quality of life. 19 Nevertheless, some patients avoid exercise following a cardiac-related diagnosis or event 7 due to uncertainty about safety and appropriateness and lack of support. 4,35 This was echoed in our study; a number of respondents noted that although they were eager to do physical activity, with limited personalised guidance they were afraid they may push themselves too far, restricting the amount of exercise they were mentally comfortable doing.…”
Section: Discussionmentioning
confidence: 99%
“…This could mitigate some of the mental health challenges people face, as studies have shown the interplay between physical activity and mental wellbeing. 19,42 There have been encouraging developments in this area since we conducted our study, with the NHS Long Term Plan prioritising cardiac rehabilitation, 38 particularly for patients with heart failure and heart valve disease. 43 However, our results indicate that for this to be impactful, people need personalised guidance about the type and amount of exercise that is appropriate for them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aquatic therapy may provide an ideal environment for gait training and other rehabilitative exercises in people post-stroke. The effectiveness of aquatic interventions is well established in the elderly population (Barela et al, 2006, Barela andDuarte, 2008) as well as people post-stroke (Chu et al, 2004, Noh et al, 2008, Aidar et al, 2013. The previous studies have reported that aquatic therapy improved walking speed, paretic lower extremity strength and even psychological measures such as depression and anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…Iwamoto et al (2009) found that exercise and physical activity improved balance, flexibility, muscle strength and walking ability in older people (Iwamoto et al, 2009). Water-based training is also one of the methods that has been taken into consideration by sports and rehabilitation specialists in recent years (Aidar et al, 2013).This exercise is a series of specialized exercises that involve the body and the brain in a way that it affects power, endurance, and flexibility. Due to the presence of features such as hydrostatic pressure, floatation and deep sense of sensation, water environment can be an ideal environment for physical exercises (Shiri, Karppinen, Leino-Arjas, Solovieva, & Viikari-Juntura, 2009).…”
Section: Introductionmentioning
confidence: 99%